Quality, IT and Business Operations Modeling and Optimization (Singapore : Springer Singapore, 2018)
This book discusses action-oriented, concise and easy-to-communicate goals and challenges related to quality, reliability, infocomm technology and business operations. It brings together groundbreaking research in the area of software reliability, e-maintenance and big data analytics, highlighting the importance of maintaining the current growth in information technology (IT) adoption in businesses, while at the same time proposing process innovations to ensure sustainable development in the immediate future. In its thirty-seven chapters, it covers various areas of e-maintenance solutions, software architectures, patching problems in software reliability, preventive maintenance, industrial big data and reliability applications in electric power systems. The book reviews the ways in which countries currently attempt to resolve the conflicts and opportunities related to quality, reliability, IT and business operations, and proposes that internationally coordinated research plans are essential for effective and sustainable development, with research being most effective when it uses evidence-based decision-making frameworks resulting in clear management objectives, and is organized within adaptive management frameworks. Written by leading experts, the book is of interest to researchers, academicians, practitioners and policy makers alike who are working towards the common goal of making business operations more effective and sustainable.
A Conceptual Architectural Design For Intelligent Health Information System: Case Study On India -- A General Framework For Modeling Of Multiple Version Software With Change Point -- An Improved Scoring System For Software Vulnerability Prioritization -- Analysis Of Feature Ranking Techniques For Defect Prediction Software Systems -- Analysis Of Impediments To Sustainability In Food Supply Chain: An Interpretive Structural Modeling Approach -- Analysis Of Module Based Software Reliability Growth Model Incorporating Imperfect Debugging And Fault Reduction Factor -- Analytics For Maintenance Of Transportation In Smart Cities -- Business Strategy Prediction System For Market Basket Analysis -- Defending the OSN-Based Web Applications from XSS Attacks using Dynamic JavaScript Code and Content Isolation -- Defending The Osn-Based Web Applications From Xss Attacks Using Dynamic Javascript Code And Content Isolation -- Development Of Qfd Methodology -- Discrete-Time Framework For Determining Optimal Software Release And Patching Time -- Efa-Ftopsis Based Assessment Of Service Quality: Case Of Shopping Websites -- Finding Efficiency In Data Envelopment Analysis Using Variable Reduction Technique -- Fire Safety Experimental Investigations Of Time To Flashover As A Function Of Humidity In Wood -- Fixing Of Faults And Vulnerabilities Via Single Patch -- Lc-Elm Based Gray Scale Image Watermarking In Wavelet Domain -- Implementing And Evaluating R-Tree Techniques On Concurrency Control And Recovery With Modifications On Non-Spatial Domains -- Inventory Decisions For Imperfect Quality Deteriorating Items With Exponential Declining Demand Under Trade Credit And Partially Backlogged Shortages -- Maintenance In The Era Of Industry 4.0: -- Issues And Challenges -- Modeling Fault Detection Phenomenon In Multiple Sprints For Agile Software Environment -- Optimal Price And Warranty Length For Profit Determination: An Evaluation Based On Preventive Maintenance -- Six Sigma Implementation In Cutting Process Of Apparel Industry -- Forecasting Of Major World Stock Exchanges Using Rule Based Forward And Backward Chaining Expert Systems -- Performance Enhancement Of Aodv Routing Protocol Using Anfis Technique -- Preservation Of Qos And Energy Consumption Based Performance Metrics Routing Protocols In Wireless Sensor Networks -- Reliability Analysis For Up-Graded Software With Up-Dates -- Quantitative Software Process Improvement Program Using Lean Methodology -- Selection Of Optimal Software Reliability Growth Models: A Fuzzy Dea Ranking Approach -- Significance Of Parallel Computation Over Serial Computation Using Openmp, Mpi And Cuda -- Software Release And Patching Time With Warranty Using Change Point -- Two-Dimensional Framework To Optimize Release Time & Warranty -- Technological Capabilities Impacting Business Intelligence Success In Organizations -- Testing Time And Effort Based Successive Release Modeling Of A Software In The Presence Of Imperfect Debugging -- The Role Of Educational Erp In The Isomorphic Development Of The Newly Started Higher Education Institutions -- When to Start Remanufacturing Using Adopter Categorization.
Business and Management
text file PDF
Keywords: Big data; Production management; Quality control; Reliability; Industrial safety; Management; Industrial management